Dolutegravir Resistance in Malawi's National HIV Treatment Program. (5th April 2022) - van Oosterhout, Joep J; Chipungu, Chifundo; Nkhoma, Lyse; Kanise, Hope; Hosseinipour, Mina C; Sagno, Jean Babtiste; Simon, Katherine; Cox, Carrie; Hoffman, Risa; Steegen, Kim; Matola, Bilaal W; Phiri, Sam; et al.
Abstract: Dolutegravir HIV drug resistance (HIVDR) data from Africa remain sparse. We reviewed HIVDR results of Malawians on dolutegravir-based antiretroviral therapy (November 2020–September 2021). Of 6462 eligible clients, 33 samples were submitted to South Africa, 27 were sequenced successfully, and 8 (30%) had dolutegravir HIVDR. Malawi urgently requires adequate HIVDR testing capacity.